Clinico-histopathological evaluation of tonsillectomy specimens at a tertiary care hospital - Modh, Nikita; Khilnani, Ajeet Kumar; Lanjewar, Dhaneshwar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Tonsillar diseases are common in paediatric and adult otolaryngological practice and often require tonsillectomy and specimens are subjected to histopathological evaluation. Chronic tonsillitis is disease with repeated attacks of acute tonsillitis/ a sub-clinical form of a resistant or poorly treated infection. Aim of study was to determine the most common histopathological findings in patients presenting with clinical features of chronic tonsillitis. Methods: The present study is an observational study carried out at the Departments of Pathology and Otorhinolaryngology at Gujarat Adani Institute of Medical Sciences and GK General Hospital, Bhuj from January 2019 to April 2022. Results: A total of 35 cases of bilateral tonsillectomy were studied in a span of 40 months. There were 17 (49%) males and 18 (51%) females. The age ranges of the patients varied from 7 to 37 years with maximum number of cases less than 20 years of age. A total of 70 specimens obtained from 35 patients were studied. The most common clinical presentation was throat pain in 29 (83%) patients. The histopathological evaluation confirmed chronic tonsillitis in 40 (57%) specimens, followed by chronic lymphoid hyperplasia/ hypertrophy in 30 (43%) specimens, 14 specimens with chronic tonsilitis showed associated actinomycetes. Conclusions: Resected tonsillectomy specimens should be routinely evaluated by histopathological examination to know the cause of enlarged tonsils.